2006
DOI: 10.1038/nature05470
|View full text |Cite
|
Sign up to set email alerts
|

Categorization of behavioural sequences in the prefrontal cortex

Abstract: Although it has long been thought that the prefrontal cortex of primates is involved in the integrative regulation of behaviours, the neural architecture underlying specific aspects of cognitive behavioural planning has yet to be clarified. If subjects are required to remember a large number of complex motor sequences and plan to execute each of them individually, categorization of the sequences according to the specific temporal structure inherent in each subset of sequences serves to facilitate higher-order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
159
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(170 citation statements)
references
References 28 publications
11
159
0
Order By: Relevance
“…Previous studies have shown that frontal lobe neurons encode complex motor sequences based on conditional sensory cues stored in working memory (39)(40)(41). Therefore, an important role of the frontal lobe, notably prefrontal and premotor cortices, is the readout of information in working memory at the service of complex behavior (39).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that frontal lobe neurons encode complex motor sequences based on conditional sensory cues stored in working memory (39)(40)(41). Therefore, an important role of the frontal lobe, notably prefrontal and premotor cortices, is the readout of information in working memory at the service of complex behavior (39).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lPFC neurons coded the spatial endpoints during tracking of a maze more often than the individual movements to be performed (Saito et al, 2005). More recently, lPFC neurons were found to represent the category of temporal patterns constituting a series of actions (Shima et al, 2007). In view of the wealth of abstractlevel coding of actions demonstrated in previous reports, the action-selective activity of lPFC neurons found in this study likely codes the action substantially in an abstract sense; in particular, it likely represents an intentional aspect of action to capture the target on the screen rather than specifying movement itself.…”
Section: Representation and Processing Of Information For Action Specmentioning
confidence: 99%
“…In the behavioural paradigms applied in these studies, the temporal sequence of movements was instructed visually and, in most cases, memorized by the monkeys so that it could be repetitively reproduced, before moving on to another sequence of targets, and so on. Still in monkeys (Barone and Joseph, 1989;Funahashi et al, 1993;Ninokura et al, 2004;Shima et al, 2007;Berdyyeva and Olson, 2010), a fairly comparable representation of motor sequencing was found in the dorsolateral prefrontal cortex (dlPFC). A role played by SMA in the control of motor sequences has also been found in human subjects (e.g., Gerloff et al, 1997;Boecker et al, 1998;Deiber et al, 1999;Lepage et al, 1999;Schubotz and Von Cramon, 2001;Verwey et al, 2002;Van Mier et al, 2004;Bengtsson et al, 2004;Kennerley et al, 2004;Tanaka et al, 2010).…”
Section: Introductionmentioning
confidence: 99%